The Digital Transformation in Circulation Service Librarian Performance at the Regional Library and Archives Service of Jambi Province - Perananda, M Yusril; Miliani, Masyrisal; Riady, Yasir (Mitra Palupi, 2024)
Background: Public libraries must be able to provide services that can support quality in order to increase interest in visiting libraries. Purpose: This study describes how the performance and quality of librarians on circulation services at the Regional Library and Archives Service of Jambi Province. What are the librarian's obstacles in improving the performance of the circulation service, What are the librarian's efforts to improve the performance of the circulation service. This study also describes a general picture of how things are at the Jambi Provincial Library and Archives Service, especially in circulation services. Design and methods: The method used in this research is qualitative with a descriptive approach. Determination of subjects in this study by means of purposive sampling, data collection through observation, interviews, and documentation. Data analysis methods are data reduction, data presentation, and drawing conclusions. The results obtained from this study were concluded after triangulating the data. Results: The results obtained from this study were concluded after triangulating the data. The results in this study indicate that the performance of librarians in Circulation Services at the Regional Library and Archives Service of Jambi Province is quite good, although not yet fully optimal. This can be seen from the Employee Work Targets and performance indicators which include work quality, quantity, timeliness, effectiveness, and independence. Obstacles of librarians in improving the performance of circulation services, namely: Lack of human resources, inadequate facilities and infrastructure. The librarian's efforts in improving the performance of circulation services, namely: Adding management human resources, adding and improving facilities and infrastructure. The performance of librarians in Circulation Services at the Regional Library and Archives Service of Jambi Province is quite good, although it is not fully maximized and can be improved again to achieve excellent service quality